GAMBARAN PENGETAHUAN MENGGUNAKAN MEDIA VIDEO ANIMASI TENTANG MENYIKAT GIGI TERHADAP DEBRIS INDEKS PADA SISWA/I KELAS IV SD NEGERI 101818 KEC. PANCUR BATU - Aisyah Aulia; Yenny Lisbeth Siahaan; Intan Aritonang (Poltekkes Kemenkes Medan, 2025)
Knowledge encompasses knowing, understanding, application, analysis, synthesis, and evaluation.To increase awareness and change students' attitudes and behavior regarding proper tooth brushing, this study aims to describe the impact of animated video media on tooth brushing knowledge and its effect on the debris index.This descriptive research used a survey method, with a sample of 32 fourth-grade students at SDN 101818, Pancur Batu Sub-district. Data were collected through questionnaires and debris index examinations both before and after an educational intervention using a 1-minute animated video. The results showed an increase in students' knowledge after the intervention. Before the education, only 28.2% of students had good knowledge, which increased to 83.3%afterward. Meanwhile, those in the poor category decreased from 21.8% to 0%. For the debris index, before the education,none met the good criterion, 43.7% were moderate, and 56.3% were poor. After the education, 62.5% met the good criterion, 37.5% were moderate, and none were poor. Animated video media proved effective in increasing students' knowledge about tooth brushing and reducing their debris index scores. It is hoped that this media can be more widely used in dental health education in elementary schools.